BAHASA DALAM MASYARAKAT: SUATU KAJIAN SOSIOLINGUISTIK - ., Nuryadi (Fakultas Komunikasi, Sastra, dan Bahasa, 2010)
This paper discusses about language in society which spreads horizontally and vertically. Horizontally or geographically, this paper explain why we speak differently in different regions. That means language consists of many dialects spreading horizontally. Some differences come from word choices, the pronunciation of words, and grammatical rules. Vertically socially, this paper explain why we speak differently in different social status. Some differences are due to age, sex, profession and whether English is a first language or not. Explaining the way people use language in different social contexts provides a wealth of information about the way language work, as well as about the social relationships in a community. This paper explore many aspects of language in society such as regional and social dialect, standard language, style, register, slang, jargon, argot, lingua franca, pidgin, Creole, and taboo